Analysis of Effects of Nutrition and Physical Appearance on Self-Confidence in Women who Exercise - Başaran, Zekiye (Progress in Nutrition, 2022)
The purpose of this study was to analyze the effect of nutrition and physical appearance perfectionism on self-confidence in women who exercise. This is an experimental study without a control group. The research sample consisted of 36 women. The study was carried out for 10 weeks, 3 days a week, and 1 hour a day. The program consisted of step, pilates, zumba, yoga, and cardio work. Data were obtained face-to-face and online. Personal information form, women self-confidence scale, physical appearance perfectionism scale, and the three-factor eating questionnaire were utilized as data collection tools. SPSS 25 packaged software analyzed the data obtained from scales. Paired Sample t-test was applied to data showing normal distribution while the Wilcoxon test was applied to data showing non-parametric distribution. There also was conducted a correlation analysis to determine the relationship between scales. According to research results, there are decreases in weight, waist measurement, and BMI (Body Mass Index) values of the participants. While there is a decrease in all averages in nutritional status, a significant difference can be seen between uncontrolled eating and conscious restriction pre/post-test. There also is a significant difference in the physical appearance perfectionism total point and imperfection sub-dimension. A significant difference can be observed in total and social sub-dimension while there are decreases in self-confidence points. There is a significant relationship between women's self-confidence and physical appearance perfectionism. Finally, exercise and conscious nutrition cause a decrease in weight, body mass index, and waist measurement, while it creates a positive effect on physical appearance. These effects also increased the level of self-confidence in women. There is a significant relationship between physical appearance and self-confidence. It is recommended that all women be directed to sports activities so that they can be strong and self-confident.Keywords: Exercise, Nutrition, Physical appearance, Self-confidence